CHARACTERIZATION AND QUANTIFICATION OF ENDOGENOUS PHAGES OF LACTICASEIBACILLUS RHAMNOSUS JB-1 - Jose, Tamina Angel (My University, 2025)
Lacticaseibacillus rhamnosus JB-1 is a strain recognized for its beneficial effects on eukaryotic host. This study aims to identify and characterize dormant bacterial viruses or prophages with the JB-1 genome, determine their capacity to be released as bacteriophages. We also investigate the membrane vesicles released from JB-1 and detect bacteriophages within these preparations. Bioinformatic analysis of the JB-1 genome predicted the presence of three prophage regions. Experimental validation demonstrated spontaneous release of two of these phages, which were also detected along with membrane vesicles and found systemically circulating. Genomic characterization included sequence annotation, determination of exact start/end points, analysis of gene function and comparison with other related bacteriophages. The JB-1 CRISPR-Cas system was also identified and characterized which will contribute to a deeper understanding of the potential for future manipulation of this probiotic microorganism. Morphological characterization was conducted using transmission electron microscopy to determine capsid shape, size, tail length, to classify the phages based on these features. To overcome limitations in quantifying phages lacking suitable hosts for propagation, a qPCR-based method was developed and validated. Furthermore, the stability of JB-1 phages was studied under a range of temperature and pH conditions relevant to the gastrointestinal tract.
Keywords: Phages; Prophages; Lacticaseibacillus